Dosage, time, and polytherapy dependent effects of different levetiracetam regimens on cognitive function - Jon Davis Perkins (17885747) (2023)
Objective Cognitive impairment is a potential drawback of antiseizure medications. This study aimed to evaluate the impact of different levetiracetam drug regimens on cognitive function. Methods A retrospective analysis identified 221 patients diagnosed with seizures who underwent cognitive screening. Patients were categorized into four groups: no medications, non-levetiracetam medications, high and low dose levetiracetam. Composite scores determined low and high levetiracetam groups whereby one point was added for each increment in dosage, duration since uptake, and concurrent anti-seizure medication. Variables known to affect cognition were recorded and classified as demographic, seizure-related, diagnosis-related, and psychopathology. Logistic regression was used to identify variables associated with cognitive scores below cut-off. Results Multivariable analysis found being male, non-active in the community, less than 12 years of education, left temporal lobe epilepsy, high seizure frequency, and depression were associated with poor cognitive performance. In a final regression analysis, the high levetiracetam group exhibited a 4.5-fold higher likelihood of scoring below cut-off than the medication-free group (OR 4.5, CI 1.5–13.6, p<.08). Depression (OR 2.1, CI 1.1-3.9, p<.03), being male (OR 2.2, CI 1.1-4.3, p<.02), and not being active in the community (OR 3.8, 1.6-8.7, p <.003) remained significant contributors to the model. Language (p<.05), attention (p<.05), and delayed recall (p<.001) were the most affected cognitive domains. Significance When taken in small doses, for brief periods as monotherapy, levetiracetam minimally influences cognition. At higher doses, as part of long-term seizure management, in conjunction with multiple ASMs, LEV is associated with cognitive impairment. Other Information Published in: Epilepsy & Behavior License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.yebeh.2023.109453